Epitaxial growth and crystalline properties of Ge1−x−ySixSny on Ge(0 0 1) substrates. (August 2015) - Asano, Takanori; Terashima, Tatsuya; Yamaha, Takashi; Kurosawa, Masashi; Takeuchi, Wakana; Taoka, Noriyuki; Nakatsuka, Osamu; Zaima, Shigeaki
Abstract: We have investigated the influence of tensile and compressive strain on the crystalline structures of Ge1− x − y Si x Sn y epitaxial layers. The tensile strain in Ge1− x − y Si x Sn y induces a non-uniform crystallinity of (2 2 0) lattice planes and surface roughening despite the strain magnitude is as small as 0.20%. In contrast, the unstrained or compressive strained Ge1− x − y Si x Sn y layer exhibits a flat and uniform surface and high crystallinity. We found that the control of the sign of the strain is an important factor to obtain a high quality Ge1− x − y Si x Sn y layer. Furthermore, substitutional Sn atoms in Ge1− x − y Si x Sn y epitaxial layer with an Sn content of 10% are thermally stable for annealing at 500 °C.